Design of Electrode Coatings for Bimetallic Welds - Bhandari, Deepak (My University, 2017)
The use of bimetallic welds between plain carbon steel and austenitic stainless steel being in nuclear power plants imposes a challenge towards the structural integrity assessment for researchers not only due to the different metallurgical zones, having a gradient in chemistry and mechanical properties but also due to the high temperature operating conditions and the temperature variations over the period of operation. In the bimetallic welds the use of Ni-base weld metal significantly decreases the extent of carbon migration from the ferritic steel into the weld, because of the low carbon activity gradient between the ferritic steel and the weld metal, and the low diffusivity of carbon in Ni-base alloys. Hence, the Ni-base weld metals are commonly used for fabrication and repair of bimetallic weld joints. The only drawback of Ni-base weld metal is their inferior weldability compared to austenitic stainless steels, as a consequence, there are fewer welders qualified to weld with it. Further, the nuclear welds with Ni-base welds metals are also not immune to failure, and service failure of these nuclear welds have also been reported. Nucleation and propagation of creep cracks along a planar array of globular carbides formed during service have been considered responsible for many such failures. The difference in melting temperatures of the two metals that are to be joined must always be considered. Solidification and contraction of the metal with the higher melting temperature will induce stresses in the other metal while it is in a weak, partially solidified condition. This problem may be solved by depositing one or more layers of a filler intermediate melting temperature on the face of the base metal with the higher melting temperature. This procedure is known as buttering. The weld is then made between the buttered face other base metal. The buttering layer should serve to reduce the melting temperature differential. Buttering may also be used to provide a transition between materials with substantially different coefficients of thermal expansion and to act as a barrier layer that will slow the migration of undesirable elements from the base metal to the weld metal during service at elevated temperatures. The work in this thesis is aimed at developing electrode coatings for bimetallic welds and providing a comparative assessment of the three layer and two layer approaches involving mild steel and stainless steel buttering layers.
PhD thesis
Keywords: Bimetallic weld; Electrode coatings; Mixture design; Mechanical properties